Discrete-event simulation of a production process for increasing the efficiency of a newspaper production. (April 2019) - Riskadayanti, O; Yuniaristanto,; sutopo, W; Hisjam, M
Abstract: One of the characteristics of the newspaper industry is the cycle time of production is limited. The production time cycle is depending on several aspects, namely the quantity of paper produced, as well as the utility of each machine and operator. Because of the cycle time of production is limited, the production process of a newspaper industry is required to have a high level of efficiency so that the level of productivity can be increased. A high level of efficiency can be achieved by optimizing aspects of raw materials, machines, and operators. In this article, the method used for modelling real-time production floor systems is Discrete Event Simulation (DES). DES is done by representing the interaction between all components in the system as an event. Flexsim software used to model the actual production system. Analysis of the results of the simulation conducted to determine the utility level of each machine. In this article, there are three scenarios simulated. Each scenario is replicated ten times. Scenario 1 is the scenario of the current system, then the scenario 2 and 3 are proposed as improvements of composition newspaper production systems. From 2 improvements scenarios, the scenario 3 was chosen to be the best scenario that could improve the efficiency of newspaper production systems.